Foreign Under-Investment in US Securities and the Role of Relational Capital - Bryane Michael (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Over 70 academic papers attempt to explain why foreigners invest in US securities. All ignore the vital role of the US broker-dealer. Macroeconomic factors like a trade balance or corporate governance may guide foreign investors toward certain markets. But US broker-dealers provide information to foreign investors and execute the actual trades. We hypothesize that particular foreign investors under-invest in US securities because of a lack of relational capital with US broker-dealers. We find that broker-dealer marketing intensity in foreign markets partly explains foreigners' decisions to invest in US securities. We also estimate "pent-up" demand for US securities in developing countries – like China, Argentina, Turkey and Russia –equals roughly half-a-trillion dollars. Such pent-up demand - represented as a convergence gap with investment-to-GDP ratios in highly developed capital markets – helps predict which markets these broker-dealers are likely to invest marketing effort in the future. As such, broker-dealers interested in assisting foreign investors find the right securities for their portfolios should not focus on big, rich economies. They should focus on economies with the largest convergence gaps. We also find that broker-dealers must take in account the effect their marketing effort has on the typical variables (like relative returns, risks, asymmetric shocks and communication with the US) when they use these screening variables in deciding where to build their relational capital (and place their sales effort) in any year.
Keywords: F21; G11; 330; portfolio investment; us securities; Foreign portfolio investment; Financial investment